Spremljanje funkcijske neodvisnosti v rehabilitacijski bolnišnici: primer učinkovite uporabe preprostega modela zmesi porazdelitev - Vidmar, Gaj (Informatica Medica Slovenica, 2009)
An application of a mixturedistribution model of two bounded Gaussians on datagathered by assessing patients undergoing complex inpatient rehabilitationusing Functional Independence Measure (FIM) at admission and discharge is presented. Even though the model is simple, it has notable explanatory and practical value.
Keywords: Delovna sposobnost, ocenjevanje; Disability Evaluation; Normal Distribution; Normalna distribucija; Rehabilitacija; Rehabilitacijski centri; Rehabilitation; Rehabilitation Centers; Treatment Outcome; Zdravljenje, izid